2005
DOI: 10.1007/s00296-005-0081-4
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic skin responses in reflex sympathetic dystrophy

Abstract: This study was performed to determine the utility of sympathetic skin response (SSR) in evaluating the sympathetic function and to follow up the effects of sympathetic blockade in reflex sympathetic dystrophy (RSD). Thirty patients having RSD with upper extremity involvement were randomly divided into two groups. Besides medical therapy and exercise, physical therapy agents were applied to both the groups. In addition to this treatment protocol, stellar ganglion blockade was done by diadynamic current in Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 8 publications
0
18
0
2
Order By: Relevance
“…Many studies have shown increased amplitude and decreased latency in hemiplegic patients and in reflex sympathetic dystrophy patients as a sign of sympathetic overactivity. [23,24] There are contradictory results regarding SSR latencies. Some studies have reported the intra-individual variations for amplitudes (2-48%) and latencies (2-22%).…”
Section: Discussionmentioning
confidence: 93%
“…Many studies have shown increased amplitude and decreased latency in hemiplegic patients and in reflex sympathetic dystrophy patients as a sign of sympathetic overactivity. [23,24] There are contradictory results regarding SSR latencies. Some studies have reported the intra-individual variations for amplitudes (2-48%) and latencies (2-22%).…”
Section: Discussionmentioning
confidence: 93%
“…The final sample consisted of nine randomized placebo- or active-controlled [40, 43–50] and four quasi-randomized [5154] trials published between 1994 and 2014 with a total sample size of 440 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the conventional nerve blockade technique, noninvasive SGB is free from potential complications such as infection, bleeding, potential nerve damage, and other adverse events that may be caused by an injective or a puncture injury following repeated applications [19–29]. Moreover, noninvasive SGB can be conveniently performed in clinical practice even in the absence of an anesthesiologist and is well tolerated by patients without any thermal injury or with few adverse effects [31, 39, 40, 43–56], regardless of the application modality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative sensory testing, the quantitative sudomotor axon reflex test, and the cold pressor test combined with thermographic imaging have been used for the assessment of sympathetic nervous system function. 29 Electroneurodiagnostic sudomotor testing, 30 the sympathetic skin response test, 31 and thermography alone have been used to assess sympathetic nervous system activity. 32 Clinical findings remain the gold standard for the diagnosis of CRPS I, 33 and the tests described above may serve as additional tools to establish the diagnosis in doubtful cases.…”
Section: Discussionmentioning
confidence: 99%